Real-World Performance of Integrative Clinical Genomics in Pediatric Precision Oncology - Pokorna, Petra; Palova, Hana; Adamcova, Sona; Jugas, Robin; Al Tukmachi, Dagmar; Kyr, Michal; Knoflickova, Dana; Kozelkova, Katerina; Bystry, Vojtech; Mejstrikova, Sona; Merta, Tomas; Trachtova, Karolina; et al. (Laboratory investigation, 2024)
Despite significant improvement in the survival of pediatric patients with cancer, treatment outcomes for high-risk, relapsed, and refractory cancers remain unsatisfactory. Moreover, prolonged survival is frequently associated with long-term adverse effects due to intensive multimodal treatments. Accelerating the progress of pediatric oncology requires both therapeutic advances and strategies to mitigate the long-term cytotoxic side effects, potentially through targeting specific molecular drivers of pediatric malignancies. In this report, we present the results of integrative genomic and transcriptomic profiling of 230 patients with malignant solid tumors (the "primary cohort") and 18 patients with recurrent or otherwise difficult-to-treat nonmalignant conditions (the "secondary cohort"). The integrative workflow for the primary cohort enabled the identification of clinically significant single nucleotide variants, small insertions/deletions, and fusion genes, which were found in 55% and 28% of patients, respectively. For 38% of patients, molecularly informed treatment recommendations were made. In the secondary cohort, known or potentially driving alteration was detected in 89% of cases, including a suspected novel causal gene for patients with inclusion body infantile digital fibromatosis. Furthermore, 47% of findings also brought therapeutic implications for subsequent management. Across both cohorts, changes or refinements to the original histopathological diagnoses were achieved in 4% of cases. Our study demonstrates the efficacy of integrating advanced genomic and transcriptomic analyses to identify therapeutic targets, refine diagnoses, and optimize treatment strategies for challenging pediatric and young adult malignancies and underscores the need for broad implementation of precision oncology in clinical settings.
Keywords: Young Adult; Male; lékařská onkologie; kohortové studie; Child, Preschool; Neoplasms; mladý dospělý; Cohort Studies; Adolescent; Infant; Child; individualizovaná medicína; dítě; mužské pohlaví; Genomics; stanovení celkové genové exprese; mladiství; Gene Expression Profiling; předškolní dítě; lidé; ženské pohlaví; Humans; kojenec; nádory; Precision Medicine; Female; Medical Oncology; genomika